2019
DOI: 10.35967/jipn.v17i1.7054
|View full text |Cite
|
Sign up to set email alerts
|

Politik Identitas dan Negara Bangsa di Riau

Abstract: Riau Vision 2020, regional regulations on Lembaga Adat Melayu[LAM] Riau, the issue of sons and non-sons of the region in regional head elections are the main characteristic of the ongoing revival of the Political Identity of the era of regional autonomy in Riau. The Rise of Identity Politics in Riau is considered to be at odds with the nation-state whose essence is recognizing diversity. The politics of identity in this context is considered to jeopardize the development of the diversity-based nation-state [na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Frequently, identity politics are employed to rally and empower communal groups. Ethnic ties play a vital part in identity politics, become potential cultural icons, and serve as a source of strength for political acts (Erman & Albintani, 2018). Malay as a method of communication is a pretty simple description; language has numerous dimensions.…”
Section: Languagementioning
confidence: 99%
“…Frequently, identity politics are employed to rally and empower communal groups. Ethnic ties play a vital part in identity politics, become potential cultural icons, and serve as a source of strength for political acts (Erman & Albintani, 2018). Malay as a method of communication is a pretty simple description; language has numerous dimensions.…”
Section: Languagementioning
confidence: 99%
“…The use of political language based specifically on the idea of "Kemerdekaan" probably indicates that the nationalist idea itself, based on the institutionalization of the nationalist movement in the form of the creation of a new nation state, was not so popular among the Indonesian radical left, who preferred to play on the feelings of the social but not national discontent. At the same time, the communists sought to use Islam for their own purposes (Erman & Albintani, 2018).…”
Section: Ethnic Mobility In Indonesiamentioning
confidence: 99%
“…Identity politics in this context is understood as an opportunity for participation in politics as an individual or group power struggle based on identity associated with race, ethnicity, gender, and religion. Sometimes regional sentiment due to the exploitation of the issue of "indigenous people" between local residents and immigrants often becomes an issue in Indonesian politics (Erman & Albintani, 2018).…”
Section: A Introductionmentioning
confidence: 99%
“…In essence, identity politics in Indonesia is more specific to issues of race, culture, politics, and local preferences expressed by elites through the accumulation of their respective interests (Abdullah, 2017). The Regional Division Movement is considered a form of identity politics in the era of decentralization (Albintani, 2018). Also, the politics of local identity becomes thicker because eeach region wants to be led by indigenous of his area (Prayetno, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Asrinaldi & Azwar, 2018) explains that the involvement of the Riau Malay community in the regional elections is adjusting on how the Malay culture can be maintained and used by governor in running the government. Then, other research explains that in the context of identity politics, the 2020 vision and mission of Riau has the potential to cause ethnic-ideological clashes and social identity issues that do not run linearly because of political interests based on cultural institutions (Albintani & Marta, 2020;Albintani, 2018). From some of the studies above, it has identified that the previous studies had concentrated more on issues of indigenous and cultural-based political interests.…”
Section: Introductionmentioning
confidence: 99%